Silver diamine fluoride compared to atraumatic restorative technique for the treatment of caries in primary and mixed first phase dentition - Juan Pablo Vargas; Macarena Uribe; Duniel Ortuño; Francisca Verdugo-Paiva (Medwave, 2020)
INTRODUCTION Cavitated carious lesions in primary and mixed dentition require prompt treatment to control caries progression. Silver diamine fluoride has emerged as an alternative to the atraumatic restorative technique due to its easy application. However, there is still uncertainty regarding its effectiveness and safety.